2018
DOI: 10.1016/j.respe.2018.05.313
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of subclinical micronutrient deficiency in German older adults: Results from the population-based KORA-Age study

Abstract: Subclinical micronutrient deficiency in older adults is associated with chronic age-related diseases and adverse functional outcomes. In Germany, the older population is at risk of insufficient micronutrient intake, but representative studies on micronutrient status in old and very old adults are scarce. This study's objectives were to estimate the prevalence of subclinical vitamin D, folate, vitamin B 12 and iron deficiencies among older adults, aged 65 to 93, from the KORA-Age study in Augsburg, Germany (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Using data from the National Health and Nutrition Examination Survey (NHANES), 6.9% of US adults aged 51–70 years and 15% of those over 70 years are B12 deficient [ 17 ]. Similar findings were reported in Germany, with 27.3% of people aged 65–93 having deficient serum B12 levels [ 30 ]. The decline in gastric acid secretion that occurs with advancing age can make it difficult to absorb food-bound B12 in meat, poultry, seafood, dairy, and eggs.…”
Section: Life In the Margins: The Health Impact Of Micronutrient Insusupporting
confidence: 86%
“…Using data from the National Health and Nutrition Examination Survey (NHANES), 6.9% of US adults aged 51–70 years and 15% of those over 70 years are B12 deficient [ 17 ]. Similar findings were reported in Germany, with 27.3% of people aged 65–93 having deficient serum B12 levels [ 30 ]. The decline in gastric acid secretion that occurs with advancing age can make it difficult to absorb food-bound B12 in meat, poultry, seafood, dairy, and eggs.…”
Section: Life In the Margins: The Health Impact Of Micronutrient Insusupporting
confidence: 86%
“…However, there is a lack of a Polish population-wide research of people over 65 in the field of vitamin and micronutrient assessment in the body. In representative German studies, the KORA-Age-Study conducted in a group of people over 65 (n = 1,079, aged 65-93), deficiencies of vitamin 25 (OH) D (<50 nmol / l) were found in 52% of respondents and vitamin B12 (<221 pmol / l) in 27.3% of subjects [13].…”
Section: Introductionmentioning
confidence: 99%
“…Conzade et al (2017) examining data among older adults, aged 65 to 92, from the KORA-Age study in Augsburg, Germany (1079 participants), using serum nutritional biomarkers and multiple logistic regression, concluded that more than a quarter of individuals had low vitamin B12 levels. Furthermore, they revealed that conditions such as aging, lack of physical activity, frailty, no use or irregular use of micronutrient-containing supplements consist common predictors of subclinical micronutrient deficiencies[ 32 ]. Soh et al (2020), in another study among 2938 participants (1400 men and 1538 women) from the Korean Frailty and Aging Cohort Study with mean age of 77.8 years for the frail group and 76.7 for the non-frail group, concluded that low B12 levels increased the incidence of frailty and also affected physical performance[ 33 ].…”
Section: Investigating the B12-frailty Interplaymentioning
confidence: 99%